Poro-Elasto-Plastic Model for the Wave-Induced Liquefaction - Liao, C.; Zhao, Hongyi; Jeng, Dong-Sheng (Journal of Offshore Mechanics and Arctic Engineering, 2015)
In this paper, we presented an integrated numerical model for the wave-induced pore pressures in marine sediments. Two mechanisms of the wave-induced pore pressures were considered. Both elastic components (for oscillatory) and the plastic components (for residual) were integrated to predict the wave-induced excess pore pressures and liquefaction in marine sediments. The proposed two-dimensional (2D) poro-elasto-plastic model can simulate the phenomenon of the pore pressure buildup and dissipation process in a sandy seabed. The proposed model overall agreed well with the previous wave experiments and geo-centrifuge tests. Based on the parametric study, first, we examined the effects of soil and wave characteristics on the pore pressure accumulations and residual liquefaction. Then, a set of analysis on liquefaction potential was presented to show the development of liquefaction zone. Numerical example shows that the pattern of progressive waves-induced liquefaction gradually changes from 2D to one-dimensional (1D), while the standing wave-induced liquefaction stays in a 2D pattern in the whole process. No Full Text